Impact of Sensitization on Waiting Time Prior to Kidney Transplantation in Germany. Issue 12 (2nd August 2022) - Zecher, Daniel; Zeman, Florian; Drasch, Thomas; Tieken, Ineke; Heidt, Sebastiaan; Haasnoot, Geert W.; Vogelaar, Serge; Rahmel, Axel; Banas, Bernhard
Abstract : Background: Assignment of unacceptable HLA mismatches (UAMs) prevents transplantation of incompatible grafts but potentially prolongs waiting time. Whether this is true in the Eurotransplant Kidney Allocation System (ETKAS) and the Eurotransplant Senior Program in Germany is highly debated and relevant for UAM policies. Methods: Donor pool restriction due to UAM was expressed as percent virtual panel-reactive antibodies (vPRAs). Kaplan-Meier estimates and multivariable Cox regression models were used to analyze the impact of vPRA levels on waiting time and transplant probability during a period of 2 y in all patients eligible for a kidney graft unter standard circumstances in Germany on February 1, 2019 (n = 6533). Utility of the mismatch probability score to compensate for sensitization in ETKAS was also investigated. Results: In ETKAS, donor pool restriction resulted in significant prolongation of waiting time and reduction in transplant probability only in patients with vPRA levels above 85%. This was most evident in patients with vPRA levels above 95%, whereas patients in the acceptable mismatch program had significantly shorter waiting times and higher chances for transplantation than nonsensitized patients. In the Eurotransplant Senior Program, vPRA levels above 50% resulted in significantly longer waiting times and markedly reduced the chance for transplantation. Compensation for sensitization by the mismatch probability score was insufficient. Conclusions: Donor pool restriction had no significant impact on waiting time in most sensitized patients. However, despite the existence of the acceptable mismatch program, the majority of highly sensitized patients is currently disadvantaged and would benefit from better compensation mechanisms. Abstract :